Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To find the value of [tex]\( f(2) + f(-1) \)[/tex] for the function [tex]\( f(x) = x^2 - 5x + 1 \)[/tex], we need to follow these steps:
1. Calculate [tex]\( f(2) \)[/tex]:
Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2^2 - 5(2) + 1 \][/tex]
Simplify the expression step by step:
[tex]\[ 2^2 = 4 \][/tex]
[tex]\[ -5(2) = -10 \][/tex]
Combining these, we get:
[tex]\[ f(2) = 4 - 10 + 1 \][/tex]
[tex]\[ f(2) = -5 \][/tex]
2. Calculate [tex]\( f(-1) \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = (-1)^2 - 5(-1) + 1 \][/tex]
Simplify the expression step by step:
[tex]\[ (-1)^2 = 1 \][/tex]
[tex]\[ -5(-1) = 5 \][/tex]
Combining these, we get:
[tex]\[ f(-1) = 1 + 5 + 1 \][/tex]
[tex]\[ f(-1) = 7 \][/tex]
3. Add the results of [tex]\( f(2) \)[/tex] and [tex]\( f(-1) \)[/tex]:
Now, we need to add [tex]\( f(2) \)[/tex] and [tex]\( f(-1) \)[/tex]:
[tex]\[ f(2) + f(-1) = -5 + 7 \][/tex]
4. Final Result:
[tex]\[ f(2) + f(-1) = 2 \][/tex]
So, the value of [tex]\( f(2) + f(-1) \)[/tex] is [tex]\( \boxed{2} \)[/tex].
1. Calculate [tex]\( f(2) \)[/tex]:
Substitute [tex]\( x = 2 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 2^2 - 5(2) + 1 \][/tex]
Simplify the expression step by step:
[tex]\[ 2^2 = 4 \][/tex]
[tex]\[ -5(2) = -10 \][/tex]
Combining these, we get:
[tex]\[ f(2) = 4 - 10 + 1 \][/tex]
[tex]\[ f(2) = -5 \][/tex]
2. Calculate [tex]\( f(-1) \)[/tex]:
Substitute [tex]\( x = -1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = (-1)^2 - 5(-1) + 1 \][/tex]
Simplify the expression step by step:
[tex]\[ (-1)^2 = 1 \][/tex]
[tex]\[ -5(-1) = 5 \][/tex]
Combining these, we get:
[tex]\[ f(-1) = 1 + 5 + 1 \][/tex]
[tex]\[ f(-1) = 7 \][/tex]
3. Add the results of [tex]\( f(2) \)[/tex] and [tex]\( f(-1) \)[/tex]:
Now, we need to add [tex]\( f(2) \)[/tex] and [tex]\( f(-1) \)[/tex]:
[tex]\[ f(2) + f(-1) = -5 + 7 \][/tex]
4. Final Result:
[tex]\[ f(2) + f(-1) = 2 \][/tex]
So, the value of [tex]\( f(2) + f(-1) \)[/tex] is [tex]\( \boxed{2} \)[/tex].
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.
A train traveled 720km in 9h. How far would it travel in 11 hr? How long would it take to go 1120km?